THE RELATIONSHIP BETWEEN FINANCIAL FLEXIBILITY AND CASH LIQUIDITY: AN EMPIRICAL STUDY IN A SAMPLE OF IRAQI PRIVATE BANKS - Arshad Abdul Amir Jassem Al- Shammari, Inas Hussin Alwan Al Yahya (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Due to the rapid progress of technology, businesses, both political and economic, from the beginning of the twentieth century to the outside environment has been a microcosm of the world for these organizations, which means service or productivity. At any level, from horizontal systems to the upper levels to inter-organizational dealings, these were a challenge. For the survival and growth of these organizations, it is important for them to work on long-term plans that embrace the cash provided by the dealers so that the potential fall and rise in funding options that can be made accessible to them. These banks, represented by their departments, are impacted by changes on one side and by stress due to considerations and concerns on the other. public debt, and cash flow (investment). in order to achieve the goals of the report, the information on the Iraq Exchange was used in the Iraqi private sector between two factors from January 1st of 2019 to December 31st of 2019, and using certain financial and mathematical tools, the results indicate that there is a strong association between the two. The findings in this report are consistent with the proposed theory, and recommendations. The most important of these is that banks in the Iraqi banking sector should realize that their financial leverage is closely linked to their percentage of equity, which gives an indication of their sources of financing.